Potential contribution of pineal atrophy and pineal cysts toward vulnerability and clinical characteristics of psychosis - Takahashi, Tsutomu; Sasabayashi, Daiki; Takayanagi, Yoichiro; Higuchi, Yuko; Mizukami, Yuko; Akasaki, Yukiko; Nishiyama, Shimako; Furuichi, Atsushi; Pham, Tien Viet; Kobayashi, Haruko; Noguchi, Kyo; Suzuki, Michio (NeuroImage clinical, 2021)
•Pineal morphology was investigated in schizophrenia patients and ARMS subjects.•Pineal volumes were significantly smaller in both groups than in healthy controls.•Pineal cysts were associated with clinical symptomatology in schizophrenia.•Pineal morphology may reflect vulnerability and the clinical subtype of psychosis. Magnetic resonance imaging (MRI) studies reported pineal gland atrophy in schizophrenia patients and individuals at a clinical high risk of developing psychosis, implicating abnormalities in melatonin secretion in the pathophysiology of psychosis. However, it currently remains unclear whether the morphology of the pineal gland contributes to symptomatology and sociocognitive functions. This MRI study examined pineal gland volumes and the prevalence of pineal cysts as well as their relationship with clinical characteristics in 57 at risk mental state (ARMS) subjects, 63 patients with schizophrenia, and 61 healthy controls. The Social and Occupational Functioning Assessment Scale (SOFAS), the Schizophrenia Cognition Rating Scale (SCoRS), and the Brief Assessment of Cognition in Schizophrenia (BACS) were used to assess sociocognitive functions, while the Positive and Negative Syndrome Scale was employed to evaluate clinical symptoms in ARMS subjects and schizophrenia patients. Pineal gland volumes were significantly smaller in the ARMS and schizophrenia groups than in the controls, while no significant differences were observed in the prevalence of pineal cysts. Although BACS, SCoRS, and SOFAS scores were not associated with pineal morphology, patients with pineal cysts in the schizophrenia group exhibited severe positive psychotic symptoms with rather mild negative symptoms. The present results indicate the potential of pineal atrophy as a vulnerability marker in various stages of psychosis and suggest that pineal cysts influence the clinical subtype of schizophrenia.